Penerapan Google Maps API dan Formula Haversine Pada Aplikasi Ambulance Rakyat - Eko Budi Susanto; Paminto Agung Christianto; Mohammad Reza Maulana; Bambang Ismanto (JURIKOM (Jurnal Riset Komputer), 2022)
Emergency measures to treat trauma patients really need to be done so that they can be handled properly, one that can be used to deal with this problem is the availability of an ambulance.Utilization of Google Maps API technology can be implemented in applications to assist residents of Kota Pekalongan in getting access to ambulance transportation through the Ambulance Rakyat application. The Ambulance Rakyat is a type of Android-based panic button application that is used to find and call an ambulance based on the user's closest location. In this research, the Ambulance Rakyat application has been built that implements the Haversine formula and the Google Maps API. The test results show that the Ambulance Rakyat application can find the location of the nearest ambulance, and the application can display a map of the location of the user and ambulance driver. Based on tests conducted by application developers, the application has been in accordance with the needs of users